Evidence, Explanation, and the Pursuit of Truth in Literature and Law. (October 2019) - Johnson, Jeffery
My focus is evidence. I understand this concept to be the marshalling of facts (data, etc.) in support of some position. This might be a district attorney presenting evidence to a jury that O. J. is guilty, or a literary critic arguing that Hamlet suffered from an Oedipus complex. But what is the logical connection between the relevant facts and the position they are being used to defend? How are we to distinguish successful cases of the marshalling of evidence – good arguments – from unsuccessful cases – weak arguments? I defend what I take to be a very commonsensical and pedagogically useful theory of [good] evidence. I argue that this view, inference to the best explanation, captures most, if not all, appeals to evidence in everyday contexts, as well as quite specialized domains like science, detective reasoning, and criminal and civil evidence. It also nicely encapsulates the sort of evidence that jurists and critics marshal in defense of particular readings of legal and literary texts. Appeals to evidence in the complicated worlds of teenage romance, detective fiction, criminal law, literary interpretation, and constitutional law all nicely fit the structure and evaluative methodology of inference to the best explanation. But only the diagnoses of lipstick stains, murder victims and bloody gloves can be held to the standards of correspondence and metaphysical realism. Literary and constitutional texts can be explained, and can be better or worse explained, but the truth or falsity of these interpretations is firmly in the realm of the coherence theory.